Tradisi Ijazah Hadis Musalsal bil Muṣāfaḥah di Pesantren Jami’atul Qur’an Grogol Kediri - Karima Nurul Huda; Aliifatur Roudhotul Jannah; Yenni Lailatul Rosidah; Lintang Dewi Agustin (Canonia Religia, 2023)
This research aims to uncover the tradition of granting Ijazah (certificates of authorization) for musalsal bil musafahah Hadith practiced at Jami’atul Qur’an Islamic Boarding School. The research questions to be answered include: how is the implementation and interpretation of the tradition of Ijazah for musalsal Bil musafahah Hadith within the pesantren community, and what is the role of the local leader in the transmission and transformation of this ijazah tradition from the perspective of Peter L. Berger's social construction theory? This study utilizes a qualitative approach and applies a descriptive method. To analyze the central role of the subject or local leader (Kiai Samsul Hadi), the researcher attempts to apply Peter L. Berger and Thomas Luckmann's social construction theory.The granting of Ijazah for musalsal bil musafahah Hadith at Pesantren Jami’atul Qur’an takes place during the month of Ramadan and is directly given by the Kiai to the attending students. Initially, the transmission of the Musalsal Hadith was obtained by Kiai Samsul from prominent scholars from around the world and Indonesia, including Sheikh Yasin al-Fadani, Kiai Mahrus ‘Aly, Kiai Idris Marzuqi, and Kiai Yasin Asymuni. The basis for the Ijazah and the Hadith being transmitted is the narration that "whoever shakes hands with me or greets me with a handshake will enter paradise on the Day of Judgment." The acceptance of this tradition is closely related to the content of the Hadith, which promises heavenly rewards for those who engage in the practice of musafahah (handshaking). Despite the Hadith being considered weak in terms of its authenticity, the tradition is still preserved because it is based on the belief in the blessings associated with the act of shaking hands and the intention to continue the knowledge acquired from one's teacher, for the sake of seeking blessings and connecting with righteous actions. [Penelitian ini bertujuan untuk mengungkap tradisi ijazah hadis musalsal bil muṣāfaḥah yang dipraktikkan di Pesantren Jami’atul Qur’an. Rumusan masalah yang hendak dijawab antara lain: bagaimana pelaksanaan dan pemaknaan atas tradis ijazah hadis musalsal bil muṣāfaḥah di kalangan komunitas pesantren serta bagaimana pula peran local leader dalam transmisi dan transformasi tradisi pengijazahan tersebut dalam perspektif teori konstruksi sosial Peter L. Beger. ? Penelitian ini menggunakan pendekatan kualitatif dengan  menerapkan metode deskriptif. Untuk menganalisis bagaimana peran sentral subjek atau local leader (Kiai Samsul Hadi), peneliti berusaha menggunakan teori konstruksi social Peter L.Berger dan Thimas Lockmann.  Ijazah hadis musalsal bil muṣāfaḥah di Pesantren Jami’atul Qur’an dilakukan pada bulan Ramadhan dan diberikan secara langsung oleh Kiai kepada para santri yang hadir. Pada mulanya pengijazahan hadis musalsal diperoleh Kiai Samsul dari ulama-ulama besar dunia dan Indonesia di antaranya Syaikh Yasin al-Fadani, Kiai Mahrus ‘Aly, Kiai Idris Marzuqi, hingga Kiai Yasin Asymuni. Landasan pengijazahan dan hadis yang diijazahkan yaitu man ṣafāḥanī aw ṣāfaḥa man  ṣafāḥanī ilā yawm al-qiyāmah dakhala al-jannah. Penerimaan atas tradisi inipun berkaitan erat dengan muatan kandungan hadis, yakni tentang keutaman ber-musafahah berupa jaminan pahala surga bagi yang melakukannya. Meskipun berkualitas dla’if, tradisi tetap dilestarikan karena pertimbangan yang digunakan adalah dari aspek tabarrukan kepada amal orang-orang shalih dan menyambungkan ilmu yang ia dapat kepada guru.]